Dynamic Incentives for Optimal Control of Competitive Power Systems - Kölsch, Lukas (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
This work presents a real-time dynamic pricing framework for future electricity markets. Deduced by first-principles analysis of physical, economic, and communication constraints within the power system, the proposed feedback control mechanism ensures both closed-loop system stability and economic efficiency at any given time. The resulting price signals are able to incentivize competitive market participants to eliminate spatio-temporal shortages in power supply quickly and purposively.